STUDY OF THE TENDENCY TO TREATMENT OF PATIENTS WITH CHRONIC DISEASES OF THE CARDIOVASCULAR AND RESPIRATORY SYSTEM (Symposium on Life and Environmental Sciences, 2026)
The article examines the adherence to treatment among the population living in the district center, using the example of Samarkand region, for hypertension, ischemic heart disease, chronic heart failure, bronchial asthma, and chronic obstructive pulmonary diseases. This indicator was assessed using the widely used Morisky-Green questionnaire in the world. The reasons for patients' low propensity for treatment were indicated. Non-compliance with indications that are directly related to the patient and insufficient interaction between the doctor and the patient. Successful management of chronic diseases requires not only effective treatment but also active patient participation in the treatment process. One of the main factors determining the effectiveness of treatment for non-communicable chronic diseases is predisposition to treatment. Improving this indicator will help improve the quality of life of patients, reduce the number and duration of hospitalizations, costs, and mortality.
Keywords: Hypertension, ischemic heart disease, chronic heart failure, bronchial asthma, chronic obstructive pulmonary disease, predisposition to treatment.